A new species of marsupial frog (Anura: Hemiphractidae: Gastrotheca) from the Andes of southern Peru - Duellman, William E.; Catenazzi, Alessandro; Blackburn, David C. (Zootaxa, 2011)
Gastrotheca nebulanastes sp. nov. from cloud forests in the upper Kosñipata Valley, Manu National Park, in the Andes of southern Peru is similar to G. excubitor, which inhabits grasslands in higher elevations than the cloud forests. The two species differ in relative lengths of the fingers, skin texture, coloration, and advertisement call. Although the new species has an elevational range of 2000–3300 m, it is most abundant at 2400–2800 m. A phylogenetic analysis of a previously defined clade of Gastrotheca based on a fragment of 16S mitochondrial gene provides strong support that the sister taxon to the new species is G. atympana, a species from farther north in the Cordillera Oriental in Peru.